Il «maraviglioso» e il «maravigliosissimo» dei tempi moderni - Anna Chiara Luzzi (Flaubert: Revue Critique et Génétique)
In the early 20th century cinema considerably pervaded the cultural field, and mingling with literature it created artistic hybrids, a trend that would continue throughout the century. With Cabiria, a silent movie directed by Pastrone and written by D’Annunzio, the multimedia dimension of film found its most successful expression. The movie is a synthesis and a rewriting of literary topoi inherited primarily from Flaubert’s Salammbô, but also from other writers such as Salgari and his Cartagine in fiamme, and of painters such as Sargent or musicians like Reyer, themselves influenced by the French novel. This article will go back over the stages of this colossal movie’s making, by studying the film’s recurrent motifs and highlighting the analogies and differences with Flaubert’s founding work.